If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(10 + -5v) = 0 (10 * 2 + -5v * 2) = 0 (20 + -10v) = 0 Solving 20 + -10v = 0 Solving for variable 'v'. Move all terms containing v to the left, all other terms to the right. Add '-20' to each side of the equation. 20 + -20 + -10v = 0 + -20 Combine like terms: 20 + -20 = 0 0 + -10v = 0 + -20 -10v = 0 + -20 Combine like terms: 0 + -20 = -20 -10v = -20 Divide each side by '-10'. v = 2 Simplifying v = 2
| 14-2x-16=5x-3x+34 | | 6(4z-2)=36 | | -40-8v=-5(1+3v) | | -7x-8y=-2 | | -39.6=12-0.4s | | 4x+9=-x+4 | | -17+16-x=16 | | 2y-x=y-5 | | 0.25+.05=6.10 | | 5b^2-22b-15=0 | | 18+8t=9(t-2) | | 3h-12=11h+4 | | 8(-9-2+3v-6v)= | | 2(4)-y=2 | | -6x-4(-7x-13)=58 | | 2(3)-y=2 | | y+2.6=6.9 | | 4x-22=54 | | -n-5(-6-7)=-119 | | 4x^2+20x+25=64 | | -9(1+6+6v)= | | 100=x+(x+2) | | 4h-4=8 | | 61.94+56.06-x-45=38 | | -3(-2+9v)= | | -16t^2+18t+10=0 | | -7(n-5)-6n=4n+1 | | 6(2x+3)=11x-3-6x | | 2x^2+10y=-7 | | 11b+3=25 | | t^2-16t+64= | | (2z+1)+9=(6z-9) |